The Implications for Consumer Protection Against Online Loans in the Spotlight of Civil Law - Silvani Nur Rahmat Lukum; Nur Mohamad Kasim; Weny Almoravid Dungga (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Online lending has become an increasingly popular financial solution in Indonesia, providing easy access to funds for people who are not fully served by traditional financial institutions. Despite offering many conveniences, the rapid growth of online lending brings various risks, such as the rise of illegal online loans, high interest rates, and the potential misuse of users' personal data. This research aims to analyze consumer protection in online loan transactions, by reviewing existing regulations, such as Law No. 8/1999 on Consumer Protection, OJK Regulation No. 77/Pojk.01/2016, and the Electronic Information and Transaction Law (ITE Law). This research uses a normative legal research method with a statutory approach that prioritizes legal materials in the form of laws and regulations as the main reference. Data collection techniques are carried out through library research, analyzing relevant regulations and related literature. The results show that although these regulations already exist, the implementation of supervision and law enforcement is still weak, resulting in many violations harming consumers. Stricter supervision from OJK, strict sanctions against illegal fintech providers, and increased education to the public about their rights as consumers are needed. With more effective supervision and clearer regulations, it is hoped that the online lending industry can develop healthily and provide benefits without harming consumers.